Characters in hypno teaching and neuroscience: an overview - Achmad Setya Roswendi; Ahmad Khoiri; Denok Sunarsi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
Moral degradation as an indicator of the weak character of students who represent the character of the nation is increasingly concerning, the study aims to identify characters through Hypno teaching and neuroscience studies. Literature research with a systematic review through previous research in the years 2010-2019. The results showed that the contribution of Hypno teaching is very important in realizing student character through the cognitive development of children's brains. Student characters are motivation, self-efficacy, empathy, and sympathy for others. the contribution of the research is great hope for the life of the nation in the future in realizing a golden generation of character.